2015
DOI: 10.25015/penyuluhan.v10i1.9908
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Eksistensi Kearifan Lokal Huyula Desa Bongoime Provinsi Gorontalo

Abstract: <p>This study aims to analyze the existence of local wisdom Huyula measured by knowledge, attitudes and behavior of farmers to Huyula and its relationship with the internal and external factors farmers. The sample was Bongoime villagers who work as rice farmers. This study uses quantitative data with qualitative data furnished. This study tested using Spearman rank correlation test with significance level 0,05 level. Results of this study indicate that Huyula is a values contained in the mutual aid socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Dalam konteks lain, ada budaya Mo'huyula, yang merupakan bentuk gotong royong untuk menyelesaikan pekerjaan atau permasalahan tertentu tanpa pamrih. Budaya ini telah lama dipraktikkan oleh para luluhur sebagai bentuk sistem ekonomi yang terkoordinir dan sukarela (Annas & Wahyuni, 2014).…”
Section: Hasil Dan Pembahasan Dimensi Kultural Dan Implementasi Kebij...unclassified
“…Dalam konteks lain, ada budaya Mo'huyula, yang merupakan bentuk gotong royong untuk menyelesaikan pekerjaan atau permasalahan tertentu tanpa pamrih. Budaya ini telah lama dipraktikkan oleh para luluhur sebagai bentuk sistem ekonomi yang terkoordinir dan sukarela (Annas & Wahyuni, 2014).…”
Section: Hasil Dan Pembahasan Dimensi Kultural Dan Implementasi Kebij...unclassified
“…Kearifan lokal adalah semua bentuk pengetahuan, keyakinan, pemahaman atau wawasan serta adat kebiasaan atau etika yang menuntun perilaku manusia dalam kehidupan di dalam komunitas ekologis (Keraf, 2002). Pentingnya mengkaji kearifan lokal di Negara berkembang seperti Indonesia, dimana kearifan lokal terutama di bidang pertanian banyak ditemukan (Annas & Wahyuni, 2014). Kearifan lokal jika digali dan dikaji dari sebuah masyarakat bisa menjadi sebuah solusi bagi pengelolaan sumber daya alam yang optimal khususnya di bidang pertanian (Lisdiana, et al, 2018).…”
Section: Pendahuluanunclassified
“…It could be seen that local/indigenous knowledge tend to be influenced by how the knowledge was passed down and learned by the next generations from their ancestor. Annas (2013) revealed that this process (inheritance process) could occur both vertically and horizontally. Local/indigenous knowledge comes from the values that have developed over a long time in the traditional/tribal community (Nygren 1999;Aulia and Dharmawan 2011).…”
Section: Knowledge Of Pelawan Padang Based On the Sosial Statusmentioning
confidence: 99%